A framework for developing an evidence-based, comprehensive tobacco control program - Shacham Galia; Mayshar Elana; Levin Diane; Gan-Noy Shosh; McKee Martin; Rosenberg Elliot; Rosen Laura; Borowski John; Nun Gabi; Lev Boaz (BMC, 2010)
Abstract Background Tobacco control is an area where the translation of evidence into policy would seem to be straightforward, given the wealth of epidemiological, behavioural and other types of research available. Yet, even here challenges exist. These include information overload, concealment of key (industry-funded) evidence, contextualization, assessment of population impact, and the changing nature of the threat. Methods In the context of Israel's health targeting initiative, Healthy Israel 2020, we describe the steps taken to develop a comprehensive tobacco control strategy. We elaborate on the following: a) scientific issues influencing the choice of tobacco control strategies; b) organization of existing evidence of effectiveness of interventions into a manageable form, and c) consideration of relevant philosophical and political issues. We propose a framework for developing a plan and illustrate this process with a case study in Israel. Results Broad consensus exists regarding the effectiveness of most interventions, but current recommendations differ in the emphasis they place on different strategies. Scientific challenges include integration of complex and sometimes conflicting information from authoritative sources, and lack of estimates of population impact of interventions. Philosophical and political challenges include the use of evidence-based versus innovative policymaking, the importance of individual versus governmental responsibility, and whether and how interventions should be prioritized. The proposed framework includes: 1) compilation of a list of potential interventions 2) modification of that list based on local needs and political constraints; 3) streamlining the list by categorizing interventions into broad groupings of related interventions; together these groupings form the basis of a comprehensive plan; and 4) refinement of the plan by comparing it to existing comprehensive plans. Conclusions Development of a comprehensive tobacco control plan is a complex endeavour, involving crucial decisions regarding intervention components. "Off the shelf" plans, which need to be adapted to local settings, are available from a variety of sources, and a multitude of individual recommendations are available. The proposed framework for adapting existing approaches to the local social and political climate may assist others planning for smoke-free societies. Additionally, this experience has implications for development of evidence-based health plans addressing other risk factors.